Exploring processes of teaching and learning in African university contexts: The case of education for critical thinking in Ghana, Kenya and Botswana - Pon, Carmen; Schendel, Rebecca (International Journal of African Higher Education, 2020)
This review examines recent literature about processes of teaching and learning in African higher education, focusing specifically on studies of teaching ‘for critical thinking’ in Kenya, Ghana, and Botswana. The review findings suggest that practices supporting critical thinking in African universities share a number of similarities to those highlighted in the literature published elsewhere in the world. For example, reviewed studies highlight the importance of curricular alignment, academic development, and varied assessment formats, while also acknowledging important limitations related to infrastructure, workload, and faculty and student attitudes. However, the review also exposes a crucial theoretical gap in the existing literature: the continued reliance on theories of teaching and learning that were initially developed based on studies of Western university contexts. As both teaching and learning are cultural processes, this limitation may be preventing this emerging body of literature from fully supporting universities to develop new ways of teaching that may best benefit their student populations.